Surface characterization and secondary electron yield measurement of the Ti-Zr-V films deposited on laser-etched copper. (1st August 2022) - Zhang, Wenli; Zhu, Bangle; Wang, Sihui; Fan, Le; Fang, Jianwei; Bian, Baoyuan; Li, Weimin; Wang, Yong
Abstract: The electron multipacting effect and distributed vacuum profile, induced by the interaction of the particles in vacuum chamber with the surrounding walls, are the significant issues in modern accelerators. Laser-etching the inner surface of the vacuum chambers can effectively eliminate the electron multipacting effect, and depositing the non-evaporable getter (NEG) film on the vacuum chamber walls can provide distributed pumping properties. In the present study, Ti-Zr-V NEG films were prepared by magnetron sputtering technique on laser-etched oxygen-free copper (OFC) with different deposition times. The secondary electron yields (SEY), activation kinetics, and resistance of the samples were evaluated. The results show that although the SEYs of the coated laser-etched samples are higher than those of the uncoated laser-etched sample, the maximum SEY values are still below the threshold of the operation requirements. The Ti-Zr-V film deposited on laser-etched surface exhibits obvious nucleation phenomenon with columnar microstructure and can be activated at 180^∘C. Moreover, the coated laser-etched samples present lower resistance compared with the uncoated laser-etched sample. The combination of the laser-etching technique and the NEG thin film is aim to provide a practical treatment for the vacuum chambers in modern accelerators.